New record of larval-pupal endoparasitoid Exorista deligata parasitising Indian Tea looper Hyposidra talaca from India - Sharma, Pooja V.; Das, Tamal; Mukherjee, Susmita; Pathan, Ejaj K.; Rahman, Azizur; Gathalkar, Ganesh B. (Phytoparasitica, 2024)
This is the first record of Exorista deligata (Pandell & eacute;, 1896) (Diptera: Tachinidae) as a parasitoid of Hyposidra talaca (Walker, 1860) (Lepidoptera: Geometridae) from India. H. talaca is a major and new emerging defoliator of the Tea plant Camellia sinensis (L) Kuntze (Theaceae). It completes multiple generations per year without diapause on C. sinensis, resulting in heavy crop loss. The field-collected larvae/pupa of H. talaca were checked for parasitoid infestations and reared until either the host or parasitoid emerged. The parasitoid was identified as E. deligata with morphological characteristics and confirmed by the mitochondrial cytochrome oxidase subunit-I (COX-CO1) gene sequencing technique. The parasitoid is infrequent with unexplored parasitic biology. It parasitises the larva and completes its lifecycle inside the developing H. talaca by entirely devouring the host. The mean percent parasitisation caused by E. deligata studied herein was 25.4% (range 5.88%-57.69%). Based on its parasitisation ability, we suggest the species could be a potential biological control agent to address the damage mitigation caused by the tea looper pest, H. talaca.
Keywords: Biocontrol; Exorista deligata; Hyposidra talaca; Invasive pest; Parasitisation